Pictures of Poverty: The Works of George R. Sims and Their Screen Adaptations - Jakobs, Lydia (John Libbey Publishing, 2021)
From Charles Dickens's Oliver Twist to George Sims's How the Poor Live , illustrated accounts of poverty were en vogue in Victorian Britain. Poverty was also a popular subject on the screen, whether in dramatic retellings of well-known stories or in 'documentary' photographs taken in the slums. London and its street life were the preferred setting for George Robert Sims's rousing ballads and the numerous magic lantern slide series and silent films based on them. Sims was a popular journalist and dramatist, whose articles, short stories, theatre plays and ballads discussed overcrowding, drunkenness, prostitution and child poverty in dramatic and heroic episodes from the lives and deaths of the poor. Richly illustrated and drawing from many previously unknown sources, Pictures of Poverty is a comprehensive account of the representation of poverty throughout the Victorian period, whether disseminated in newspapers, illustrated books and lectures, presented on the theatre stage or projected on the screen in magic lantern and film performances. Detailed case studies reveal the intermedial context of these popular pictures of poverty and their mobility across genres. With versatile author George R. Sims as the starting point, this study explores the influence of visual media in historical discourses about poverty and the highly controversial role of the Victorian state in poor relief.